Precursor material for electron injection layer, preparation method and application thereof
By modifying metal oxide nanoparticles with a photosensitive polarity conversion function in QLED devices, direct photolithography forming of the electron injection layer is achieved, and the problem of patterning of electron injection layer and electrical performance damage in the prior art is solved. Problem, improving the high-resolution manufacturing capability of QLED display devices.
Patent Information
- Application Number
- CN202310119919.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-08
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-02-08
AI Technical Summary
The prior art is difficult to efficiently obtain high-precision patterns of electron injection layers of QLED devices, and the traditional lithography process steps are cumbersome, which can easily damage the electrical properties of metal oxide nanoparticles.
The surface modification of metal oxide nanoparticles with photosensitive polarity conversion function is used to modify the surface modifier. Through ion exchange method, a precursor material that can change the polarity under light is formed, so as to realize direct photolithography of the electron injection layer to avoid Use photoresist.
Direct photolithography forming of electron injection layer is realized, which reduces process steps and reduces the impact of photoresist on electrical performance, and improves the high-resolution manufacturing capability of QLED display devices.
Smart Images

Figure CN116113256B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor manufacturing, and in particular to a precursor material of an electron injection layer, a preparation method and application thereof. Background Art
[0002] Quantum dot light-emitting diodes (QLEDs) have the characteristics of simple structure, high luminous efficiency, wide color gamut, and flexibility. Its structure mainly includes hole injection layer (HIL), hole transport layer (HTL), quantum dot light-emitting layer, and electron injection layer (EIL), such as Figure 1 At present, the preparation of high-resolution QLED devices has become a development trend in the future display field.
[0003] Photolithography is an effective technology for obtaining high-resolution patterns. The photoresist-free direct photolithography derived from it can simplify the process while retaining good results. Some research results have been achieved in the high-resolution pixelation technology of quantum dots, but there are few reports on direct photolithography technology for other functional layer materials.
[0004] like Figure 2 As shown, in the prior art, the traditional photolithography process steps are relatively complicated, and it is difficult to efficiently obtain a high-precision pattern of the electron injection layer of the QLED device, and the use of photoresist has a great influence on its surface electrical properties.
[0005] In QLED devices, due to the properties of the material itself, it is difficult to achieve direct photoforming of metal oxides, which are the most commonly used electron injection layers. Even if direct photoforming is achieved, it often requires a higher annealing temperature, which often has a significant negative impact on the electrical properties of the metal oxide nanoparticles, which is not worth the cost.
[0006] Therefore, the development of direct photolithography technology for electron injection layers that is suitable for QLED devices and does not cause loss of electrical performance has important application value. Summary of the invention
[0007] In view of the deficiencies of the prior art, an object of the present invention is to provide a precursor material for an electron injection layer, a preparation method and application thereof.
[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0009] In a first aspect, the present invention provides a precursor material for an electron injection layer, comprising metal oxide nanoparticles and a surface modifier modified on the surface of the metal oxide nanoparticles;
[0010] Wherein, after being exposed to light, the polarity of the surface modifier can change.
[0011] In a second aspect, the present invention further provides a method for preparing a precursor material of an electron injection layer, comprising:
[0012] Providing metal oxide nanoparticles;
[0013] Using an ion exchange method to modify the surface of the metal oxide nanoparticles with a surface modifier;
[0014] Wherein, after being exposed to light, the polarity of the surface modifier can change.
[0015] In a third aspect, the present invention further provides a method for forming an electron injection layer, comprising:
[0016] Providing a coating liquid in which the above-mentioned precursor material is dispersed;
[0017] coating the coating liquid into a film to obtain an electron injection layer precursor;
[0018] performing patterned light irradiation on the electron injection layer precursor;
[0019] The electron injection layer precursor that is not irradiated with light is cleaned and removed by using a cleaning agent with the same polarity as the solvent in the coating solution to form a patterned electron injection layer.
[0020] In a fourth aspect, the present invention further provides a light-emitting diode device, comprising a hole injection layer, a hole transport layer, a semiconductor functional layer and an electron injection layer stacked in sequence; the electron injection layer is formed by adopting the above-mentioned method for forming an electron injection layer.
[0021] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention at least include:
[0022] The precursor material provided by the present invention arranges modified molecules with a photosensitive polarity conversion function on the surface of metal oxide nanoparticles, and the polarity of the surface of the metal oxide nanoparticles changes when exposed to light, thereby changing its dissolution characteristics, so that the part of the metal oxide nanoparticles exposed to light is not easily removed by the solvent of the original polarity, thereby realizing direct photolithography of the electron injection layer;
[0023] The technical solution provided by the present invention realizes direct photoforming of metal oxide nanoparticles, avoids the use of photoresist, reduces the process steps and also reduces the influence of photoresist on the electrical properties of metal oxide nanoparticles.
[0024] The present invention contributes to the manufacture of high-resolution QLED display devices by developing pixelation technology for electron injection layer materials.
[0025] The above description is only an overview of the technical solution of the present invention. In order to enable those skilled in the art to more clearly understand the technical means of the present application and implement them according to the contents of the specification, the following is a description of the preferred embodiments of the present invention in conjunction with detailed drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the structure of a quantum dot light-emitting diode device provided by the background technology of the present invention;
[0027] Figure 2 It is a schematic diagram of a process of preparing an electron injection layer by a photoresist method provided by a typical comparative example of the present invention;
[0028] Figure 3 It is a schematic diagram of a process of preparing an electron injection layer by direct photolithography provided by a typical embodiment of the present invention;
[0029] Figure 4 This is an electron microscope photograph of the morphology of an electron injection layer prepared by direct photolithography provided in a typical embodiment of the present invention;
[0030] Figure 5 It is a schematic diagram of the structure of a quantum dot light emitting diode device provided in another typical implementation case of the present invention. DETAILED DESCRIPTION
[0031] In the prior art, there are two main methods for preparing the electron injection layer of a QLED (quantum dot light-emitting diode) device, one is a photoresist method, and the other is a photosensitive precursor (cross-linking method).
[0032] For the photoresist method, for example, metal oxide nanoparticles can be mixed with commercial photoresist and then directly patterned by ultraviolet exposure. However, this solution will cause the performance of the electron injection layer using metal oxide nanoparticles to be greatly reduced.
[0033] For the photosensitive precursor solution, the metal oxide nanoparticle precursor can be prepared by sol-gel method, for example, a photo-crosslinkable precursor (zinc dimethacrylate, zinc acrylate, etc.) is generated, a patterned precursor material is obtained by ultraviolet exposure, and then metal oxide nanoparticles are obtained by high-temperature annealing. Due to the high temperature required for annealing, this method will have adverse effects on the substrate, other functional layers or quantum dot layers.
[0034] The convenience of the above-mentioned prior art methods themselves and the performance of the prepared hole transport layer need to be improved.
[0035] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.
[0036] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0037] One aspect of an embodiment of the present invention provides a precursor material for an electron injection layer, comprising metal oxide nanoparticles and a surface modifier modified on the surface of the metal oxide nanoparticles; wherein, after being irradiated with light, the polarity of the surface modifier serving as a surface ligand can change.
[0038] The precursor material provided in the above-mentioned embodiment arranges modified molecules with photosensitive polarity conversion function on the surface of metal oxide nanoparticles. When exposed to light, the polarity of the surface of the metal oxide nanoparticles changes, and / or connects adjacent nanoparticles, thereby changing its solubility characteristics, making it difficult for the part of the metal oxide nanoparticles exposed to light to be washed and removed by solvents of the original polarity, thereby realizing direct lithography of the electron injection layer.
[0039] In some embodiments, the surface modifier can also coordinate with the adjacent metal oxide nanoparticles after being irradiated with light; some of the surface modifiers have dual photosensitive functional groups.
[0040] The coordination effect and the specific role of the "bifunctional group" simultaneously serve as the surface ligand and photosensitizer of the metal oxide nanoparticles, and both the anions and cations of some photosensitive molecules have photosensitivity properties.
[0041] In some embodiments, the surface modifier may preferably include 1,2,3,4-triazole-5-thioammonium salt, 2-(4-methyloxyphenyl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-diazo-1-naphthol-4-sulfonic acid, 1-diazo-2-naphthol-4-sulfonic acid, diphenyliodonium fluoroborate, ammonium dithiocarbamate, 1,2-naphthoquinonediazide-4-sulfonyl chloride, 2-phenyl-2-(5-((o-oxy)imino)thiophene-2-methylene)-acetonitrile , butyl dithiocarbamic acid, ammonium disulfide oxalate, N-hydroxynaphthalene imide trifluoroester, (4-methylthienyl) trifluoromethanesulfonate, triphenylsulfur trifluoromethanesulfonate, diphenyliodine trifluoromethanesulfonate, any one or a combination of two or more thereof, but not limited thereto. The above-listed compound selection range is only an exemplary selection in some preferred embodiments, and any compound with the above-mentioned functions that can be obtained by those skilled in the art based on the prior art can achieve the same technical effect based on the same principle.
[0042] In some embodiments, the metal oxide particles include any one of zinc oxide, magnesium zinc oxide, tin oxide, and titanium oxide, or a combination of two or more thereof.
[0043] In some embodiments, the mass of the surface modifier is 1-15 wt % of the mass of the metal oxide nanoparticles.
[0044] In some embodiments, the metal oxide nanoparticles have a particle size of 3-10 nm.
[0045] Another aspect of the present invention provides a method for preparing a precursor material of an electron injection layer, comprising the following steps:
[0046] Metal oxide nanoparticles are provided.
[0047] The surface modifier is modified on the surface of the metal oxide nanoparticles by using an ion exchange method.
[0048] Wherein, after being exposed to light, the polarity of the surface modifier can change.
[0049] In some embodiments, the preparation method may specifically include the following steps:
[0050] The metal oxide nanoparticles are formulated into a precursor dispersion.
[0051] The precursor dispersion and the surface modifier are uniformly mixed and ion exchange occurs to generate a precursor material for the electron injection layer.
[0052] It should be noted that the above-mentioned precursor materials can be prepared by themselves when used. For example, as in the following embodiment, before coating, the metal oxide nanoparticles are directly modified in a dispersion to form a coating liquid containing the above-mentioned precursor materials, and used in this form. It can also be a feasible implementation method that the precursor material is extracted from the above-mentioned coating liquid and used as a commodity or semi-finished product, and then reconfigured into a dispersion liquid for coating during coating, etc.
[0053] The key technical means of the present invention is the specific modification of the surface of metal oxide nanoparticles. No matter what method is used, whether it is self-made, commercially purchased or commissioned, as long as the above principles and key technical means are utilized, it should fall within the protection scope of the present invention.
[0054] See also Figure 3 Another aspect of the present invention provides a method for forming an electron injection layer, comprising the following steps:
[0055] Providing a coating liquid for dispersing the precursor material provided by any of the above embodiments;
[0056] coating the coating liquid into a film to obtain an electron injection layer precursor;
[0057] performing patterned light irradiation on the electron injection layer precursor;
[0058] The electron injection layer precursor that is not irradiated with light is cleaned and removed by using a cleaning agent with the same polarity as the solvent in the coating solution to form a patterned electron injection layer.
[0059] In some embodiments, the method for preparing the coating solution may specifically include the following steps:
[0060] Dispersing metal oxide nanoparticles in a solvent to form a dispersion;
[0061] A surface modifier is added to the dispersion to obtain the coating solution.
[0062] In some embodiments, the mass fraction of the surface modifier in the coating solution is 1-15 wt %.
[0063] In some embodiments, the mass concentration of the metal oxide nanoparticles in the coating solution is 10-60 mg / mL, preferably 25-35 mg / mL. Generally, during the synthesis process, a surface initial ligand mainly composed of hydroxyl (-OH) is formed, so that it can be well dissolved in commonly used ethanol, DMF or NMF solutions, and then subsequent ligand replacement is performed to obtain the desired coordination structure.
[0064] More specifically, the exposure wavelength of the patterned light can be adaptively adjusted according to the characteristics of the surface modifier of the photosensitive molecule, preferably ultraviolet light of 172nm-405nm.
[0065] As some typical application examples of the above technical solution, a preparation process of an electron injection layer can be as follows:
[0066] When preparing the metal oxide material precursor of the electron injection layer, the ion exchange method is used to introduce photosensitive modified substances, especially small molecules that can form bifunctional groups, which have photosensitive properties as ligands, that is, they provide stability for the nanoparticle colloid / solution and can undergo chemical transformation under the excitation of specific photon energy, making them surface modifiers of metal oxide nanoparticles. For example, 1,2,3,4-triazole-5-thioammonium salt (TTT), 2-(4-methyloxyphenyl)-4,6-bis(trichloromethyl)-1,3,5-triazine (MBT), 2-diazo-1-naphthol-4-sulfonic acid (DNS), 1-diazo-2-naphthol-4-sulfonic acid, diphenyliodonium fluoroborate, ammonium dithiocarbamate, 1,2-naphthoquinonediazide-4-sulfonyl chloride, 2-phenyl-2-(5-((o-oxy)imino)thiophene-2-methylene)-acetonitrile, butyl dithiocarbamic acid, ammonium oxalate disulfide, N-hydroxynaphthalene imide trifluoroester, (4-methylthienyl)methylphenylsulfonyl trifluoride, triphenylsulfonyl trifluoromethanesulfonate, diphenyliodonium trifluoromethanesulfonate, and the like. The introduced small molecule modifier is photosensitivity and can decompose or undergo related chemical reactions in a specific band, ultimately forming molecular modifications with the opposite polarity to the original on the surface of the metal oxide nanoparticles, changing the solubility, thereby enabling direct photolithography of the metal oxide to be achieved through development.
[0067] The mixed dispersion is formed into a film by spin coating, blade coating or dip coating, and then covered with a mask and exposed to ultraviolet light and subsequently cleaned and developed with an original polar solvent to obtain the designed pattern.
[0068] In the above technical solution, the most critical technical means is that the preferred small molecule modifier is a photosensitivity small molecule, which can also serve as a surface ligand of metal nanoparticles, and then the metal oxide with the designed pattern formed by direct photolithography technology is used as an electron injection material.
[0069] Another aspect of an embodiment of the present invention provides a light-emitting diode device, comprising a first electrode, a hole injection layer, a hole transport layer, a semiconductor functional layer, an electron injection layer and a second electrode stacked in sequence; the electron injection layer is formed by the formation method provided by any of the above embodiments.
[0070] In the above device, all layers except the electron injection layer can be manufactured by the manufacturing method in the prior art, as long as they have corresponding functions. The key point of the technical solution provided by the present invention is still the direct photolithography molding of the electron injection layer.
[0071] The technical solution of the present invention is further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only used to illustrate the present invention, and do not limit the scope of the present invention.
[0072] Example 1
[0073] This embodiment illustrates a preparation process of a QLED device, which includes the preparation process of the electron injection layer precursor material (the preparation process of the coating liquid described below includes the formation process of the precursor material) and the formation process of the electron injection layer.
[0074] In the preparation of the device, the preparation process of the patterned electron injection layer is as follows:
[0075] Preparation of coating solution: Prepare a ZnO ethanol dispersion with a mass concentration of 30 mg / ml, in which the average particle size of ZnO nanoparticles is about 5 nm. Then add 1.5 wt% of 2-(4-methyloxyphenyl)-4,6-bis(trichloromethyl)-1,3,5-triazine (MBT) photosensitizer to the above solution and mix well.
[0076] Coating film formation: The coating liquid is spin-coated and then dried to form a 30nm precursor film.
[0077] Exposure and development: Exposure to ultraviolet light with a wavelength of 365nm through a mask with a preset pattern, with an exposure dose of 150mJ / cm 2 , and finally washed and developed with anhydrous ethanol to obtain the corresponding pattern, such as Figure 4 As shown, a patterned electron injection layer is formed.
[0078] The device structure manufactured in this embodiment is as follows Figure 1 As shown, regarding the remaining layers of the device in this embodiment, the substrate is a conductive glass substrate of indium tin oxide, the hole injection layer is PEDOT:PSS with a thickness of 30nm; the hole transport layer is poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4′-(N-(4-sec-butylphenyl)diphenylamine)] (TFB) with a thickness of about 15nm; the light-emitting layer has a thickness of 20nm and is made of CdSe-based quantum dots, 20mg / ml; the electron injection layer has a thickness of 30nm and is made of ZnO; and the top electrode is a silver / aluminum composite electrode.
[0079] Figure 4It shows that the patterned electron injection layer prepared in this embodiment has a relatively regular morphology with a resolution of 2 μm, indicating that such metal oxide nanoparticles can be patterned / pixelated by direct photolithography technology, and the external quantum efficiency of the quantum dot LED device QLED device prepared in this embodiment is 11%, and the external quantum efficiency can still be maintained at 11% after being placed in an air environment for one week. .
[0080] Example 2
[0081] This embodiment illustrates a preparation process of a QLED device, which includes the preparation process of the electron injection layer precursor material and the formation process of the electron injection layer, which is generally the same as that of Example 1, and the main difference lies in the difference in the preparation of the electron injection layer.
[0082] In the preparation of the device, the preparation process of the patterned electron injection layer is as follows:
[0083] Preparation of coating solution: Prepare Zn with a mass concentration of 30 mg / ml 90 Mg 10 O ethanol dispersion, in which Zn 90 Mg 10 The average particle size of the O nanoparticles is about 5 nm. Then, 2 wt % of (4-methylthienyl) trifluoromethanesulfonate photosensitive ligand is added to the above solution and mixed evenly.
[0084] Coating film formation: The coating liquid is spin-coated and then dried to form a precursor film with a thickness of 30 nm.
[0085] Exposure and development: Then through a mask with a preset pattern under ultraviolet light with a wavelength of 254nm, the exposure dose is 120mJ / cm 2 , and finally washed and developed with anhydrous ethanol to obtain the corresponding pattern, such as Figure 4 As shown, a patterned electron injection layer is formed.
[0086] The patterned electron injection layer prepared in this embodiment is still similar to that in Embodiment 1, having a relatively regular morphology, and the external quantum efficiency of the QLED device prepared in this embodiment is 15%, and the external quantum efficiency can still be maintained at 15% after being placed in an air environment for one week.
[0087] Example 3
[0088] This embodiment illustrates a preparation process of a QLED device, which includes the preparation process of the electron injection layer precursor material and the formation process of the electron injection layer, which is generally the same as that of Example 1, and the main difference lies in the difference in the preparation of the electron injection layer.
[0089] In the preparation of the device, the preparation process of the patterned electron injection layer is as follows:
[0090] Preparation of coating solution: Prepare a ZnO ethanol dispersion with a mass concentration of 25 mg / ml, in which the average particle size of ZnO nanoparticles is about 5 nm. Then add 1.5 wt% of 2-diazo-1-naphthol-4-sulfonic acid (DNS) photosensitizer to the above solution and mix well.
[0091] Coating and film formation: The coating liquid is spin-coated and then dried to form a precursor film with a thickness of 25 nm.
[0092] Exposure and development: Exposure to ultraviolet light with a wavelength of 365nm through a mask with a preset pattern, with an exposure dose of 100mJ / cm 2 , and finally washed and developed with anhydrous ethanol to obtain the corresponding pattern, such as Figure 4 As shown, a patterned electron injection layer is formed.
[0093] The patterned electron injection layer prepared in this embodiment is still similar to that in Example 1, having a relatively regular morphology, and the external quantum efficiency of the QLED device prepared in this embodiment is 10%, and the external quantum efficiency can still be maintained at 8% after being placed in an air environment for one week.
[0094] Example 4
[0095] This embodiment illustrates a preparation process of a QLED device, which includes the preparation process of the electron injection layer precursor material (the preparation process of the coating liquid described below includes the formation process of the precursor material) and the formation process of the electron injection layer.
[0096] In the preparation of the device, the preparation process of the patterned electron injection layer is as follows:
[0097] Preparation of coating solution: Prepare SnO2 ethanol dispersion with a mass concentration of 40 mg / ml, in which the average particle size of SnO2 nanoparticles is about 5 nm. Then add 2 wt% (4-methylthienyl) trifluoromethanesulfonate photosensitive ligand to the above solution and mix well.
[0098] Coating film formation: The coating liquid is spin-coated and then dried to form a 35nm precursor film.
[0099] Exposure and development: Exposure to ultraviolet light with a wavelength of 254nm through a mask with a preset pattern, with an exposure dose of 120mJ / cm 2 , and finally washed and developed with anhydrous ethanol to obtain the corresponding pattern, such as Figure 4 As shown, a patterned electron injection layer is formed
[0100] The device structure manufactured in this embodiment is as follows Figure 1As shown, regarding the remaining layers of the device in this embodiment, the substrate is a conductive glass substrate of indium tin oxide, the hole transport layer is PEDOT:PSS with a thickness of 30nm; the hole transport layer is poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4′-(N-(4-sec-butylphenyl)diphenylamine)] (TFB) with a thickness of about 15nm; the light-emitting layer has a thickness of 20nm and is made of CdSe-based quantum dots, 20mg / ml; the electron injection layer has a thickness of 30nm and is made of SnO2; and the top electrode is a silver / aluminum composite electrode.
[0101] The patterned electron injection layer prepared in this embodiment is still similar to that in Embodiment 1, having a relatively regular morphology, and the external quantum efficiency of the QLED device prepared in this embodiment is 14%, and the external quantum efficiency remains at 14% after being placed in an air environment for one week.
[0102] Example 5
[0103] This embodiment illustrates a preparation process of a QLED device, which includes a preparation process of a patterned electron injection layer precursor material (the preparation process of the coating liquid described below includes a formation process of the precursor material) and a formation process of the electron injection layer.
[0104] In the preparation of the device, the preparation process of the patterned electron injection layer is as follows:
[0105] Preparation of coating solution: Prepare a TiO2 toluene dispersion with a mass concentration of 35 mg / ml, wherein the average particle size of the TiO2 nanoparticles is about 5 nm. Then add 2 wt% (4-methylthienyl) trifluoromethanesulfonate photosensitive ligand to the above solution and mix well.
[0106] Coating film formation: The coating liquid is spin-coated and then dried to form a 30nm precursor film.
[0107] Exposure and development: Exposure to ultraviolet light with a wavelength of 254nm through a mask with a preset pattern, with an exposure dose of 120mJ / cm 2 , and finally washed and developed with anhydrous ethanol to obtain the corresponding pattern, such as Figure 4 As shown, a patterned electron injection layer is formed
[0108] The device structure manufactured in this embodiment is as follows Figure 1As shown, regarding the remaining layers of the device in this embodiment, the substrate is a conductive glass substrate of indium tin oxide, the hole transport layer is PEDOT:PSS with a thickness of 30nm; the hole transport layer is poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4′-(N-(4-sec-butylphenyl)diphenylamine)] (TFB) with a thickness of about 15nm; the light-emitting layer has a thickness of 20nm and is made of CdSe-based quantum dots, 20mg / ml; the electron injection layer has a thickness of 30nm and is made of TiO2; and the top electrode is a silver / aluminum composite electrode.
[0109] The patterned electron injection layer prepared in this embodiment is still similar to that in Embodiment 1, having a relatively regular morphology, and the external quantum efficiency of the QLED device prepared in this embodiment is 12%, and the external quantum efficiency remains at 12% after being placed in an air environment for one week.
[0110] Example 6
[0111] This embodiment illustrates a preparation process of an inverted structure QLED device, which includes the preparation process of a patterned electron injection layer precursor material (the preparation process of the coating liquid described below includes the formation process of the precursor material) and the formation process of the electron injection layer.
[0112] In the preparation of the device, the preparation process of the patterned electron injection layer is as follows:
[0113] Preparation of coating solution: Prepare a ZnO ethanol dispersion with a mass concentration of 30 mg / ml, wherein the average particle size of ZnO nanoparticles is about 5 nm. Then add 2 wt% (4-methylthienyl) trifluoromethanesulfonate photosensitive ligand to the above solution and mix well.
[0114] Coating film formation: The coating liquid is spin-coated and then dried to form a 30nm thin film.
[0115] Exposure and development: Then expose to ultraviolet light with a wavelength of 365nm through a mask with a preset pattern, the exposure dose is 150mJ / cm2, and finally clean and develop with anhydrous ethanol to obtain the corresponding pattern, such as Figure 4 As shown, a patterned electron injection layer is formed
[0116] The device structure manufactured in this embodiment is as follows Figure 5 As shown, regarding the remaining layers of the device in this embodiment, the substrate is a conductive glass substrate of indium tin oxide, the electron injection layer is 30nm thick and is made of TiO2; the quantum dot layer is 20nm thick and is made of CdSe, 20mg / ml; the hole transport layer is CBP with a thickness of 40nm, the hole injection layer is MoO3 with a thickness of 10nm; and the top electrode is a silver / aluminum composite electrode.
[0117] The patterned electron injection layer prepared in this embodiment is still similar to that in Embodiment 1, having a relatively regular morphology, and the external quantum efficiency of the QLED device prepared in this embodiment is 13%.
[0118] Comparative Example 1
[0119] The preparation process of the quantum dot LED device in this comparative example 1 is different from that in Example 1 mainly in the preparation process of the electron injection layer.
[0120] The electron injection layer in this comparative example was prepared by the following method:
[0121] Preparation of coating solution: Prepare a ZnO ethanol dispersion with a mass concentration of 30 mg / ml, wherein the average particle size of the ZnO nanoparticles is about 5 nm.
[0122] Electron injection layer coating: Spin coating the coating solution at 2000 rpm for 30 seconds to form a ZnO film of about 30 nm.
[0123] Photoresist coating: Select commercial SU-8 series photoresist negative resist, film thickness 1.5μm,
[0124] Exposure and development: exposure wavelength 365nm, exposure dose 150mJ / cm 2 After baking at 95°C for 15 minutes, the film was developed in propylene glycol monomethyl ether acetate for 10 minutes.
[0125] Pattern etching: etching gas is oxygen (ion), flow rate is 25 sccm, RF power is 25 W, working gas pressure is 40 mTor, self-bias voltage is 140 V, and etching time is 6 min.
[0126] Resin stripping: Use hot acetone ultrasound to strip the cured photoresist, and after completion, obtain Figure 4 Similar ZnO patterns.
[0127] Since this comparative example adopts the traditional photoresist method, on the one hand, the interface contact is easily deteriorated due to photoresist residue, and on the other hand, the gas etching process is easy to have an adverse effect on quantum dots. Therefore, the electron injection layer obtained by this scheme has low performance and is difficult to be used in the preparation of QLED devices.
[0128] Comparative Example 2
[0129] The preparation process of the quantum dot LED device in this comparative example 1 is different from that in Example 1 mainly in the preparation process of the electron injection layer.
[0130] The electron injection layer in this comparative example was prepared by the following method:
[0131] Preparation of ZnO precursor solution: Dissolve zinc dimethacrylate and ethanolamine in a mixed solution of ethanol, methacrylic acid and hydrochloric acid, and the molar concentration is about 0.45M.
[0132] Coating: The coating liquid is spin-coated at 2000 rpm for 60 seconds, and then pre-baked to form a precursor film of about 140 nm.
[0133] Exposure and development: Exposure to ultraviolet light with a wavelength of 193nm through a mask with a preset pattern, with an exposure dose of 450mJ / cm 2 After the propylene alcohol development, the corresponding pattern was obtained, and the annealing treatment was performed. The final ZnO film thickness was about 60nm, forming a Figure 4 Similar ZnO patterns can be used as electron injection layers for QLED devices.
[0134] Since this comparative example adopts a method with more organic photosensitive crosslinkers, the formed film needs to be annealed at high temperature in air or oxygen-containing atmosphere to obtain the corresponding metal oxide. High temperature annealing will have adverse effects on other functional layers, especially the quantum dot layer. In addition, the energy level matching degree of the ZnO nanoparticles formed by annealing is not as good as that of the ZnO nanoparticles obtained by the solution method. Under the same test conditions, the external quantum efficiency of the QLED device provided by this comparative example is 2%, which is significantly worse than that of Example 1.
[0135] Comparative Example 3
[0136] The pixelated electron injection layer in this comparative example is prepared by the following method:
[0137] Preparation of TiO2 precursor solution: Titanium tetraisopropoxide and methacrylic acid were mixed at a molar ratio of 1:8, stirred for five minutes, then 2 ml of n-propanol was added and stirred for 10 minutes; then deionized water was added at a molar ratio of Ti to H2O of 1:20; and an appropriate amount of n-propanol was added to adjust the viscosity.
[0138] Coating: Spin coating the above coating solution at 3000rpm for 60s to form a precursor film of about 100nm.
[0139] Exposure and development: Exposure to ultraviolet light with a wavelength of 193nm through a mask with a preset pattern, with an exposure dose of 30mJ / cm 2 , and the corresponding pattern is obtained after development with cyclohexanone, forming Figure 4 Similar TiO2 patterns can be used as electron injection layers for QLED devices.
[0140] Since the comparative example needs to introduce ionized water to form the required sol when preparing the patterned TiO2 film, and water molecules have a greater negative impact on the QLED device, and the TiO2 film formed by deep ultraviolet exposure is amorphous, its conductivity is low. Therefore, under the same test conditions, the external quantum efficiency of the quantum dot LED device provided by the comparative example is 1%, which is significantly worse than that of Example 1.
[0141] Based on the above embodiments and comparative examples, it can be clearly seen that the precursor material and application method provided in the embodiments of the present invention, by setting modified molecules with a photosensitive polarity conversion function on the surface of metal oxide nanoparticles, the polarity of the surface of the metal oxide nanoparticles changes when exposed to light, thereby changing its solubility characteristics, making it difficult for the part of the metal oxide nanoparticles exposed to light to be washed and removed by solvents of the original polarity, thereby realizing direct lithography of the electron injection layer.
[0142] The technical solution provided by the embodiment of the present invention realizes direct photoforming of metal oxide nanoparticles, avoids the use of photoresist, reduces the process steps and also reduces the influence of photoresist on the electrical properties of metal oxide nanoparticles.
[0143] The embodiments of the present invention contribute to the manufacture of high-resolution QLED display devices by developing pixelation technology for electron injection layer materials.
[0144] It should be noted that the preparation method provided by the present invention is used as an electron injection layer in a QLED device, which is one of the applications of the patternable metal oxide nanoparticle technology provided by the present invention. In addition, the technical solution provided by the present invention can also be applied to the fields of nanogratings, metal oxide photolithography masks, etc.
[0145] That is, the present invention also provides the application of the above preparation method in the fields of forming electron injection layers, nano gratings, metal oxide lithography masks, etc.
[0146] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for forming an electron injection layer, characterized in that: include: providing a coating liquid in which a precursor material is dispersed; coating the coating liquid into a film to obtain an electron injection layer precursor; performing patterned light irradiation on the electron injection layer precursor; Using a cleaning agent with the same polarity as the solvent in the coating solution to clean and remove the portion of the electron injection layer precursor that has not been irradiated with light, to form a patterned electron injection layer; The precursor material includes metal oxide nanoparticles and a surface modifier modified on the surface of the metal oxide nanoparticles. After being irradiated with light, the polarity of the surface modifier can change; the surface modifier includes 1,2,3,4-triazole-5-thioammonium salt, 2-(4-methyloxyphenyl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-diazo-1-naphthol-4-sulfonic acid, 1-diazo-2-naphthol-4-sulfonic acid, diphenyl iodide Any one or a combination of two or more of onium fluoroborate, ammonium dithiocarbamate, 1,2-naphthoquinonediazide-4-sulfonyl chloride, 2-phenyl-2-(5-((o-oxy)imino)thiophene-2-methylene)-acetonitrile, butyl dithiocarbamic acid, ammonium disulfide oxalate, N-hydroxynaphthaleneimide trifluoroester, (4-methylthienyl) trifluoromethanesulfonate; the metal oxide particles include any one or a combination of two or more of zinc oxide, magnesium zinc oxide, tin oxide, and titanium oxide.
2. The forming method according to claim 1, characterized in that: The mass of the surface modifier is 1-15 wt % of the mass of the metal oxide nanoparticles.
3. The forming method according to claim 1, characterized in that: The particle size of the metal oxide nanoparticles is 3-10 nm.
4. The forming method according to claim 1, characterized in that: The preparation method of the precursor material comprises: Providing metal oxide nanoparticles; Using an ion exchange method to modify the surface of the metal oxide nanoparticles with a surface modifier; Wherein, after being exposed to light, the surface modifier can change or dissociate, resulting in a change in polarity.
5. The forming method according to claim 4, characterized in that: The preparation method of the precursor material specifically comprises: formulating the metal oxide nanoparticles into a precursor dispersion; The precursor dispersion and the surface modifier are uniformly mixed and ion exchange occurs to generate a precursor material for the electron injection layer.
6. The forming method according to claim 1, characterized in that: The preparation method of the coating liquid comprises: Dispersing metal oxide nanoparticles in a solvent to form a dispersion; A surface modifier is added to the dispersion to obtain the coating solution.
7. The forming method according to claim 6, characterized in that: The mass fraction of the surface modifier in the coating liquid is 1-15 wt %.
8. The forming method according to claim 6, characterized in that: The mass concentration of the metal oxide nanoparticles in the coating solution is 10-60 mg / mL.
9. A light-emitting diode device, comprising a hole injection layer, a hole transport layer, a semiconductor functional layer and an electron injection layer stacked in sequence; It is characterized in that The electron injection layer is formed by the formation method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Quantum dot material, patterning method of quantum dot film layer and quantum dot light-emitting device
CN112300784A
Synthetic Method for Surface Modified ZnO Nanoparticle by Alkoxy-functionalized Conjugated Polyelectrolytes and Polymer Light-Emitting Diode Using Thereof
KR1020150108092A